Different Pathways Leading up to the Same Futsal Competition: Individual and Inter-Team Variability in Loading Patterns and Preseason Training Adaptations - Anderson Santiago Teixeira; Renan Felipe Hartmann Nunes; Javier Yanci; Pascal Izzicupo; Lucinar Jupir Forner Flores; João Carlos Romano; Luiz Guilherme Antonacci Guglielmo; Fabio Yuzo Nakamura (MDPI AG, 2018)
During the preseason, futsal players deal with large internal load, which may result in a reduction in physical performance. The aims of this study were to compare the session rating of perceived exertion training load (s-RPE TL) during the preseason between two teams; and to analyze the changes on the delayed-onset muscle soreness (DOMS), aerobic- and speed-power characteristics in players accumulating different s-RPE TL (Low (LTL) vs. High (HTL)). Twenty-eight players (Team A, n = 15; Team B, n = 13) were recruited. The s-RPE TL was monitored throughout the preseason phase (five weeks) in both teams. The coaches of each team planned the activities that comprised their training programs, without any interference from the researchers. Team A evaluated countermovement jumps (CMJ) and DOMS weekly. Team B performed squat jumps (SJ), CMJ, 5 m and 15 m sprints, and a futsal intermittent endurance test (PVFIET) before and after the preseason. Team B accumulated an almost-certainly greater s-RPE TL than Team A. In Team A, the CMJ height was likely to almost certainly improved for the HTL group from week 3. In Team B, the 5 m and 15 m sprint likely decreased after the preseason. Changes in 5 m (r = −0.61) and 15 m (r = −0.56) were correlated with total s-RPE TL. Changes in PVFIET were positively associated with changes in sprint, but inversely related to the baseline. s-RPE TL differed between both teams, and substantial gains in neuromuscular performance were observed for the HTL group in Team A. Slower and faster players in Team B showed distinct intermittent-endurance and speed adaptive responses during the high-volume preseason.